Preliminary assessment on malaria-related knowledge, attitudes and practices (KAP) amongst visitors at selected recreational parks in Peninsular Malaysia - Rafidah A.,; Rohani Ahmad,; Zurainee M. N.,; Noraishah M. S., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
Malaria is a life-threatening, rampant disease and the newly emerged knowlesi malaria brings a new challenge in the management of this vector borne disease. The transmission of knowlesi malaria is closely associated with the long-tail macaque that can be easily found at near forest. Recreational park is usually located near or in the forest and therefore can be a potential area for knowlesi malaria transmission due to the nature of the recreational park which is suitable as habitat not only for long-tail macaque and mosquito that transmit the disease but also a place that is frequently visited by human population to enjoy outdoor activities. This study aims to describe the Knowledge, Attitudes and Practices (KAP) amongst visitors of recreational park with regards to malaria and its prevention. A cross-sectional survey of knowledge, attitudes and practices was conducted at three recreational parks in Malaysia namely Sungai Kedondong Recreational Park, Selangor; Sungai Tekala Reserved Forest, Selangor and Chemerong Reserved Forest, Terengganu. 460 questionnaires were distributed among parks visitors who are willing to participate in the study on voluntarily basis. Analysis were then performed on questionnaire that are filled completely by participants. Out of 460 questionnaires distributed only 296 questionnaires were filled completely. Therefore, all result presented in this study were based on 68% completed questionnaires. Majority of respondents (80.4%) knew about malaria where as high as 77% of the respondents were found to have good knowledge about malaria signs and symptoms. Around 79.1% of the respondents were aware about mosquito as the vector that transmits malaria. 62.5% of them said that malaria can be prevented by using repellent to avoid mosquito bite and 62.2% of them applied repellent before performing outdoor activities at the parks. Although the results obtained may not represent the actual situation of KAP of park visitors with regards to malaria and its prevention since the number of questionnaires analysed were relatively low, this study nevertheless able to show a pattern of good understanding among park visitors regarding malaria and its prevention. This understanding was significantly influence by participants’ level of education.